Ecological requirements of the threetoed woodpecker (Picoides tridactylus L.) in boreal forests of northern Sweden - Balasso, Michelle (2016)
The three-toed woodpecker (Picoides tridactylus L.) is a forest specialist bird, highly dependent on dead and decaying trees for foraging. I investigated the occurrence of the three-toed woodpecker in relation to vegetation characteristics including dead wood in the boreal forests of northern Sweden. Forty old forest stands were studied, were I collected data on living and dead trees, and related them to the occurrence of the three-toed woodpecker during the breeding season. Logistic regression was used to model the occurrence of the three-toed woodpecker in relation to habitat variables. I found that of all variables taken in consideration, the amount of freshly dead Norway spruce (Picea abies L.) contributed most to explaining the occurrence of three-toed woodpecker. The probability to find three-toed woodpecker in a stand increased with the basal area of freshly dead spruce, the size of the stand, the basal area of living deciduous trees and that of dying Scots pines. A probability of occurrence of 0.5 corresponded to 1.8 m²/ha of freshly dead spruce. The results refined the knowledge about three-toed woodpecker requirements, underlying the importance of spruce for foraging, and adding information on which decay stage is more preferable for the species. Taking in consideration the fact that the species is declining and included in the Swedish Red List, this study will help defining future targets for conservation management for the three-toed woodpecker.